Curriculum and learning management: Integration of creative economy value to improve students' life skill - Yes Matheos Lasarus Malaikosa; Andhika Putra Widyadharma; Widya Trio Pangestu (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2022)
The impact of the ASEAN economic community on the development of industry 4.0 is increasingly massive. The education system needs a new buzz to respond to the development of industry 4.0. The Indonesian government continues to make changes and developments in the field of education to prepare learners to become knowledgeable, capable, creative, independent, and responsible human beings. The research uses a qualitative approach, with data collection techniques through observation, interview, and one in the documentation of strengthening life skills with integrase creative economic value. In this study, researchers successfully interviewed the principal, teacher, student, and creative ruler of the alumni element of Grafika Desa Putera Vocational High School (SMK Grafika Desa Putera). The results showed that SMK Grafika Desa Putera integrates the important value of the creative economy for students in adaptive programs, local content, normative, productive, and self-development to produce productive, creative work. Vocational education aims to prepare graduates to be ready to work and innovate. The main purpose of this research is to know the content of the creative economy in shaping learners' life skills.